The european area of higher education and european citizenship - Pereira, Elisabete Monteiro de Aguiar; Passos, Rogério Duarte Fernandes dos (Universidade Estadual de Campinas, 2018)
The present article aims to recover the antecedents, as well as the trajectory of the European Space of Higher Education – ESHE – construction, pointing out that the idea of its organization predates the Bologna Process, although this was its better known face. The text seeks to compare this construction with the new idea of European citizenship. The text considers the political, legal and educational repercussions within the framework of the contemporary European concert, in the way of idealizing an enlarged European concept, as space for its projection in the globalized word educational field. It can contribute to the allocation and development of European citizenship, which is linked to the fields of culture and education, and to the establishment of a European university with harmonization of structure, curriculum, time, credits and levels of training. The EHEA formally started in 2010, although its structuring is continuing in process, either because of the specific issues of the 48 countries that comprise it, or because of the internal issues of the universities that has joined it.